Pengembangan Aplikasi Belajar Islam dengan Metode Kuis berbasis Android - Labib Alfaruqi Ibrahim; Agi Putra Kharisma; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Islamic Learning Application with the Android-based Quiz method is an Islamic religious learning application using the quiz method. There are multiple-choice quizzes, true-false quizzes, materials, work statistics, and work progress. A total of 27 respondents out of 35 respondents said that taking a quiz about Islam could help them learn Islam. From the questionnaire, the researcher makes a problem formulation that contains what the functional and non-functional requirements of the application are and whether these needs can be realized in an Android-based application. In this study, the waterfall method is used in developing its application. At the requirements analysis stage, a general description of the system will be identified, user identification, functional requirements analysis which is also depicted in use case diagrams and use case scenarios, and non-functional requirements. At the design stage, sequence diagrams, class diagrams, operation design, data design, and interface design will become a guide in implementing the application. At the implementation stage, the system implementation and interface implementation will be explained. After the application has been completed, there is a testing phase. This testing phase goes through two tests, validity testing and usability testing. In testing the validity, black box testing is used, and the results are 100% valid. In the usability test, the System Usability Scale (SUS) is used. The System Usability Scale test results obtained a total SUS score of 927.5 and an average SUS of 77.29. This category was classified as acceptable, in the good category, and classified as having a sufficient predicate.